2020
DOI: 10.1177/1758998320907116
|View full text |Cite
|
Sign up to set email alerts
|

The structural validity of the Finnish version of the Disabilities of the Arm, Shoulder and Hand: A Rasch model analysis

Abstract: Introduction The construct validity of the Disabilities of the Arm, Shoulder and Hand questionnaire (DASH) has previously been questioned. The purpose of this study was to evaluate the measurement properties of the Finnish version of the DASH for assessing disability in patients with hand complaints using Rasch Measurement Theory. Methods A cohort of 193 patients with typical hand and wrist complaints were recruited at a surgery outpatient clinic. The DASH scores were analysed using the Rasch model for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 24 publications
(40 reference statements)
1
20
0
Order By: Relevance
“…Consistent with our findings, DASH has been reported to violate the requirement of local item independence. A pattern of high residual correlation similar to ours where activity-related item group together while impairment-related items group together has been reported in patients with various upper extremity musculoskeletal disorders [ 15 , 16 , 18 , 34 , 36 , 37 ]. Similar to the approach used in the current study, Prodinger et al reported the use of two testlets (activity limitation and impairment testlets) to accommodate the issue of local dependency within the scale and this method yielded satisfactory fit to the Rasch model in line with the findings of the current study [ 34 ].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Consistent with our findings, DASH has been reported to violate the requirement of local item independence. A pattern of high residual correlation similar to ours where activity-related item group together while impairment-related items group together has been reported in patients with various upper extremity musculoskeletal disorders [ 15 , 16 , 18 , 34 , 36 , 37 ]. Similar to the approach used in the current study, Prodinger et al reported the use of two testlets (activity limitation and impairment testlets) to accommodate the issue of local dependency within the scale and this method yielded satisfactory fit to the Rasch model in line with the findings of the current study [ 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…In patients with rheumatoid arthritis, Prodinger et al reported good fit of the same 2 testlets (activity limitation and impairment testlets) used in our study providing support to the findings of the current study [ 34 ]. Studies that examined the fit of the DASH to the Rasch measurement model reported a number of misfitting items ranging from 1 to 16 items [ 15 19 , 35 40 ]. All of the misfitting items in our study have been reported in the literature to deviate from the Rasch measurement model in different upper extremity musculoskeletal populations including patients with elbow disorders, shoulder disorders, hand disorders, Dupuytren’s contracture, humeral shaft fracture, and in patients with various upper extremity disorders [ 15 19 , 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations